2008
DOI: 10.1097/aci.0b013e32830e6b04
|View full text |Cite
|
Sign up to set email alerts
|

Functions of ocular surface mucins in health and disease

Abstract: Purpose of review-The purpose of the present review is to describe new concepts on the role of mucins in the protection of corneal and conjunctival epithelia and to identify alterations of mucins in ocular surface diseases.Recent findings-New evidence indicates that gel-forming and cell surface-associated mucins contribute differently to the protection of the ocular surface against allergens, pathogens, extracellular molecules, abrasive stress, and drying.Summary-Mucins are high molecular weight glycoproteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
250
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(255 citation statements)
references
References 46 publications
3
250
0
2
Order By: Relevance
“…As the iatrogenic damage in glaucoma is mostly due to preservatives, minimizing their administration is an impelling need. Noecker and colleagues showed that antiglaucoma drugs containing low preservative concentrations were associated with less inflammatory infiltrate in the rabbit conjunctiva (Mantelli & Arg€ ueso 2008). Many clinical studies on humans confirm these laboratory results.…”
Section: Discussionsupporting
confidence: 59%
“…As the iatrogenic damage in glaucoma is mostly due to preservatives, minimizing their administration is an impelling need. Noecker and colleagues showed that antiglaucoma drugs containing low preservative concentrations were associated with less inflammatory infiltrate in the rabbit conjunctiva (Mantelli & Arg€ ueso 2008). Many clinical studies on humans confirm these laboratory results.…”
Section: Discussionsupporting
confidence: 59%
“…In addition, MUC5AC mRNA production is up-regulated in response to P. aeruginosa and its exoproducts (Li et al, 1998). The current hypothesis regarding mucin function and tear film structure is that the secreted mucins, such as MUC5AC, are part of the "first-line defence" barrier that prevents pathogens from traversing the mucosal barrier (Davidson and Kuonen 2004;Mantelli and Argüeso 2008). Our study has demonstrated that jellyfish mucins possess potential binding sites for P. aeruginosa and prevent its binding to epithelial cells grown in cell culture.…”
Section: Discussionmentioning
confidence: 93%
“…Diabetes and other metabolic diseases have also been implicated in the development of cataract. [36][37][38][39] We thus seek to state that, our oculo-visual findings may have possibly been influenced by some conditions present among the butchers and that they are not solely due to the environment in which they work. It was also confirmed that, none of the respondents in this study used any form of personal protective equipment during the singeing of the hide.…”
Section: Discussionmentioning
confidence: 99%